Evaluation of the efficacy of oxidized cellulose (surgicel) in reducing blood loss in suprapubic simple open prostatectomy: A randomized clinical trial - Reza Kazemi; Farshad Gholipour; Hanieh Salehi; Mehrdad Mohammadi Sichani; Amir Behnamfar; Majid Fathi (Journal of Research in Medical Sciences, 2023)
Background: Simple open prostatectomy is still the treatment of choice for removing large prostates; however, peri-surgical bleeding accompanied by this technique has always been a challenge for urologist surgeons. Therefore, the present study aimed to investigate the effect of surgicel on reducing bleeding in trans-vesical prostatectomy. Materials and Methods: The present double-blinded clinical trial included 54 patients with Benign Prostatic Hyperplasia (BPH), divided into two groups of 27, and underwent trans-vesical prostatectomy. After removing the prostate, the prostate adenoma was weighed in the first group. Then, two surgicel were inserted into the prostate loge for prostate adenomas weighing 75 g or less. For larger prostates, another surgicel was inserted for each 25 g weight higher than the limit of 75 g. However, no Surgicel was inserted in the control group. Other steps of the procedure were the same in both groups. Moreover, hemoglobin and hematocrit levels were assessed in both groups; preoperation, intra-operative, 24 h, and 48 h postoperative. In addition, all the fluid used for bladder irrigation was collected, and its hemoglobin level was assessed. Results: According to our results, no intergroup difference in hemoglobin level changes, hematocrit changes, International Prostate Symptom Score (IPSS), postoperative hospital stay, and number of packed cells received. However, the postoperative blood loss in bladder lavage fluid was significantly higher in the control group (120.83 ± 46.66 g) as compared to the surgicel group (72.56 ± 32.53 g) (P < 0.001). Conclusion: The present study concluded that using surgicel in trans-vesical prostatectomy could reduce postoperative bleeding without increasing the chance of postoperative complications.